2018
DOI: 10.1007/s11938-018-0168-0
|View full text |Cite
|
Sign up to set email alerts
|

POEM in the Treatment of Esophageal Disorders

Abstract: POEM is a safe and effective therapy for patients with achalasia and SED. POEM is comparable to Heller myotomy (HM) in terms of safety, efficacy, and complications, including gastroesophageal reflux disease (GERD). Outcomes of POEM are excellent even in patients who had prior failed therapies for achalasia, including failed HM and prior POEM. Recent data also suggest the efficacy and safety of POEM in both pediatric and geriatric patients. GERD after POEM is common, and the majority of patients are asymptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 98 publications
1
13
0
Order By: Relevance
“…In the elderly, on account of associated diseases, endoscopic treatment is used as the first line. The clinical success rate in our study for this subgroup was similar to the overall success rate [20,21].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the elderly, on account of associated diseases, endoscopic treatment is used as the first line. The clinical success rate in our study for this subgroup was similar to the overall success rate [20,21].…”
Section: Discussionsupporting
confidence: 84%
“…Over followup, none of the four patients required additional treatment after POEM. The efficiency of POEM for pediatric patients with achalasia seems to be better compared with pneumatic dilatation [21] with Nabi et al presenting a clinical success of POEM therapy in over 95% for patients under 18 years old [22].…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective, international, multicenter cohort study including 11 tertiary centers (2 from the United States, 7 from Europe, 2 from Asia). The total number of patients contributed by each center were as follows: Gemelli University Hospital, Italy (101), Hirslanden Private Clinic Group, Zürich (19), Deenanath Mangeshkar Hospital, India (18), Johns Hopkins Hospital, US (17), Edouard Herriot hospital, France (13), CHA Bundang Hospital, South Korea (7), Cochin Hospital, France (6), Metropolitan Hospital, Greece (5), Kingʼs College Hospital, UK (3), Iuliu Haţieganu University of Medicine and Pharmacy, Romania (2), NorthShore University HealthSystem, United States (2). Institutional Review Board approval was obtained at all institutions for chart review and patient follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Per-oral endoscopic myotomy (POEM) is a minimally invasive endoscopic technique for the treatment of achalasia and spastic esophageal disorders. It has been increasingly adopted worldwide with more than 7000 procedures performed to date [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…pneumatic dilation (PD), botox injection), and surgical procedures (i.e. Heller myotomy (HM)) 2. Since per oral endoscopic myotomy (POEM) was originally reported in 2010 by Inoue,3 POEM has been increasingly performed as one of the first‐line treatment options, and many studies have shown its safety and efficacy 4-11…”
Section: Introductionmentioning
confidence: 99%